Pengaruh Kualitas Laporan Keuangan, Debt Maturity dan Tangibility Terhadap Efisiensi Investasi Pada Perusahaan Food and Baverage yang Terdaftar di Bursa Efek Indonesia - Putu Selbita Gea Serima; Lucy Sri Musmini (Vokasi : Jurnal Riset Akuntansi, 2024)
This research was conducted to examine the following effects (1) Knowledge of taxpayers on motor vehicle tax compliance. (2) Tax sanctions against motor vehicle taxpayer compliance. (3) Drive thru SAMSAT system for motor vehicle tax compliance. This research uses the type of causal associative research. Associative research is research that serves to explain the relationship between two or more variables and causal (cause and effect) is a form of relationship between two or more variables that influence each other. The results in this study indicate that the variable taxpayer knowledge (X1) has a positive and significant effect on motor vehicle taxpayer compliance, tax sanctions (X2) has a positive and significant influence on motor vehicle taxpayer compliance, and the SAMSAT drive thru system (X3) has a positive and significant influence on motor vehicle tax compliance.